Los manuscritos del Tractatus de Terra Sancta compilatus a fratre Marino et a fratre Brocardo (anónimo): algunas notas críticas - Blanco Pascual, Cecilia (Exemplaria Classica, 2008)
This paper gives a description of both the form and the content of the two known manuscripts -ACOXVIII and BU2761- of the Tractatus de Terra Sancta compilatus a fratre Marino et a fratre Brocardo. This is an anonymous and hitherto unpublished compilation from the late Middle Ages, whose main sources are the Descriptio Terrae Sanctae written by Burchard of Mount Sion and the Liber Secretorum Fidelium Crucis super Terrae Sanctae recuperatione et conservatione written by Marino Sanuto. In this paper I also offer a hypothesis concerning the relationship between both copies of the Tractatus based on some significant textual variants.